2020
DOI: 10.1002/jbm.b.34604
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and cellular interactions of nanoporous tantalum oxide

Abstract: Tantalum possesses remarkable chemical and mechanical properties, and thus it is considered to be one of the next generation implant materials. However, the biological properties of tantalum remain to be improved for its use in tissue engineering applications. To enhance its cellular interactions, implants made of tantalum could be modified to obtain nanofeatured surfaces via the electrochemical anodization process. In this study, anodization parameters were adjusted to obtain a nanoporous surface morphology o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 32 publications
0
27
0
Order By: Relevance
“…The increase in NT diameter was also evident comparing the bottom views of the NT features (insets for Figure b,c). For the NC samples, a 1 M H 2 SO 4 + 3.3 wt % NH 4 F aqueous solution was used as the electrolyte and the anodization potential was kept constant at 20 V. Similar to previously published results in our research group, the high water content inside the electrolyte led to the formation of nanoporous surface morphology. In addition, a comparison of these findings with our previous publication showed that the formation of nanoporous structures was independent of the F-ion source used inside the electrolyte.…”
Section: Results and Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…The increase in NT diameter was also evident comparing the bottom views of the NT features (insets for Figure b,c). For the NC samples, a 1 M H 2 SO 4 + 3.3 wt % NH 4 F aqueous solution was used as the electrolyte and the anodization potential was kept constant at 20 V. Similar to previously published results in our research group, the high water content inside the electrolyte led to the formation of nanoporous surface morphology. In addition, a comparison of these findings with our previous publication showed that the formation of nanoporous structures was independent of the F-ion source used inside the electrolyte.…”
Section: Results and Discussionmentioning
confidence: 59%
“…For instance, Ma et al observed that the adhesion, proliferation, and differentiation of mouse osteocytes increased upon the decrease in NT tantalum diameter from 126 to 56 nm . A similar trend was also observed for nanoporous tantalum where surfaces having 25 nm pore size enhanced fibroblast adhesion and proliferation compared to the ones having 65 nm pore size and nonporous tantalum . The observed changes in the biological properties with changes in anodized surface feature size were not specific to tantalum; anodized NT titanium and its alloys also expressed size dependent changes in their cellular functions.…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…Fabrication of Ta 2 O 5 nanotube layers on the surface by anodization [ 195 , 196 ] or micro-arc oxidation (MAO) [ 207 ] is another approach to ameliorate the bioactivity of Ta. With the formation of nanotubes, the Ca and P elements contained in electrolytes can be incorporated into the oxide nanotubes by either of the aforementioned methods [ 208 ].…”
Section: New Development Of Porous Ta For Bone Tissue Engineeringmentioning
confidence: 99%
“…Fabrication of Ta2O5 nanotube layers on the surface by anodization [197,198] or micro-arc oxidation (MAO) [199] is another approach to ameliorate bioactivity of Ta. With the formation of nanotubes, Ca and P elements containing in electrolyte can be incorporated into the oxide nanotubes by the either aforementioned methods [200].…”
Section: Cytotoxicity (Mc3t3-e1 Cells) •mentioning
confidence: 99%